Early heart rate variability changes during acute fetal inflammatory response syndrome: An experimental study in a fetal sheep model. - Geoffroy Chevalier; Charles Garabedian; Jean David Pekar; Anne Wojtanowski; Delphine Le Hesran; Louis Edouard Galan; Dyuti Sharma; Laurent Storme; Veronique Houfflin-Debarge; Julien De Jonckheere; Louise Ghesquière (PLoS ONE, 2023)
Introduction Fetal infection during labor with fetal inflammatory response syndrome (FIRS) is associated with neurodevelopmental disabilities, cerebral palsy, neonatal sepsis, and mortality. Current methods to diagnose FIRS are inadequate. Thus, the study aim was to explore whether fetal heart rate variability (HRV) analysis can be used to detect FIRS. Material and methods In chronically instrumented near-term fetal sheep, lipopolysaccharide (LPS) was injected intravenously to model FIRS. A control group received saline solution injection. Hemodynamic, blood gas analysis, interleukin-6 (IL-6), and 14 HRV indices were recorded for 6 h. In both groups, comparisons were made between the stability phase and the 6 h following injection (H1-H6, respectively) and between LPS and control groups. Results Fifteen lambs were instrumented. In the LPS group (n = 8), IL-6 increased significantly after LPS injection (p < 0.001), confirming the FIRS model. Fetal heart rate increased significantly after H5 (p < 0.01). In our FIRS model without shock or cardiovascular decompensation, five HRV measures changed significantly after H2 until H4 in comparison to baseline. Moreover, significant differences between LPS and control groups were observed in HRV measures between H2 and H4. These changes appear to be mediated by an increase of global variability and a loss of signal complexity. Conclusion As significant HRV changes were detected before FHR increase, these indices may be valuable for early detection of acute FIRS.